Ethical Principles of Social Educator Activity - Sopova, Dana (The Modern Higher Education Review, 2025)
The article reveals the importance of ethical regulation of the social educator profession. The ethical principles of socio-pedagogical activity recorded in the code of ethics are characterised by respect for the dignity of each person, priority of the client's interests, tolerance, trust and interaction in solving the client's problems, availability of services, confidentiality, compliance with the norms of professional ethics. The social educator activity requires moral regulation of society as a specially organised and regulated activity, which involves orientation towards personality, and individuality, revealing the essential forces of a person, providing him with comprehensive social-psychological-pedagogical help in solving personal problems, in realising himself as a subject own life The Code of Ethics focuses on the observance of such ethical principles of socio-pedagogical activity as respect for the dignity of each person, priority of the client's interests, tolerance, trust and interaction in solving the client's problems, availability of services, confidentiality, compliance with the norms of professional ethics. The moral aspect of the social educator activity is revealed through a system of moral values, virtues and goodness in behaviour, which guides the observance of the norms of professional ethics in the activity of a modern social educator.